Menyembuhkan Luka Batin dengan Memaafkan - Christian Siregar (Humaniora, 2012)
Healing the inner wounds by forgiveness is an indispensable step for the recovery of one’s self so he/she can experience peace and prosperity. Both of patient (victim) and actors, they need to realize and to confess honestly and openly—in order to heal- that he/she was actually suffering from the inner wounds that areembedded in the heart, which can even be experienced by a person since he/she was in the womb, and therefore need to be take immediate action to forgive. Considering that inner wounds is a problem that can be experienced by anyone and the resulting negative impact in one's life, then the research was conducted. The study, based on a literature review indicates that there is a strong correlation between inner wounds suffered by a person with a bad past experiences. Research also shows that the inner wounds that can be healed by forgiveness. The study isexpected to be contributing to problem solving inner wounds caused by a person's past by forgiveness.